Responses of zooplankton to cane sugar additions to a small humic lake, Alinen Mustajärvi - Ewane, Basil (2010)
The response to projected increase in dissolved organic carbon (DOC) loading to boreal lakes is being studied in lake Alinen Mustajärvi, a small humic lake in southern Finland, where labile DOC concentration has been artificially increased during 2008 and 2009 by monthly additions of cane sugar. As part of this wider project, in this thesis the responses of the zooplankton community to cane sugar addition were studied. Zooplankton samples were collected monthly in the ice-free periods of 2007, 2008 and 2009 and the mean densities and mean carbon biomasses of rotifers and crustacean zooplankton (cladocerans and copepods) were calculated. Stable isotope analyses (δ13C and δ15N) were made for the crustacean zooplankton samples. Zooplankton respond to additions of DOC by an appreciable increase in the mean density of rotifers and carbon biomass of copepods, while both the mean density and carbon biomass of cladocerans showed a decrease between years. Values for δ13C increased progressively across the years, especially for cladocerans, but less so for copepods. This suggests strongly that appreciable DOC from sugar additions was being transferred to zooplankton by heterotrophic bacteria and zooplankton dependence on heterotrophic bacteria appeared to increase with the increased loading of DOC in lake Alinen Mustajärvi.